Mechanical properties and its reliability prediction of engineered /strain-hardening cementitious composites (ECC/SHCC) with different moisture contents at negative temperatures. (November 2022) - Huo, Yanlin; Sun, Huayang; Chen, Zhitao; Yang, Yingzi
Abstract: The mechanical properties of cement-based materials with different moisture contents are very sensitive to temperature. It is well known that engineered/strain-hardening cementitious composites (ECC/SHCC) are a high ductility cementitious composite material. The current research on SHCC is limited to room temperature and high temperature, and there is still a gap in the research on negative temperature. This study aims to explore the mechanisms of compressive strength and tensile properties of SHCC serving in cold environments. The effects of key parameters such as temperature (20 °C, −20 °C, −40 °C, and −60 °C) and moisture content (0%, 50%, 80%, and 100%) on the properties of SHCC were investigated comprehensively. With decreasing temperature and increasing moisture content, the compressive and tensile strengths of SHCC increased, while the tensile strain capacity decreased significantly. However, the tensile strain capacity of SHCC is still greater than 2% even at −60 °C. Micromechanical model parameters were obtained by fracture toughness and single fiber pullout tests, and the Pseudo Strain Hardening Behavior (PSH) criterion was calculated to explain the strain properties deterioration of SHCC at negative temperatures. Reliability prediction of the tensile strain capacity of SHCC at negative temperatures was made based on the Weibull distribution. The predicted results agree well with the experimental results. The predicted method can guide the design and engineering applications of SHCC in severe cold environments. Highlights: Assessment of compressive strength and tensile properties of SHCC at negative temperatures. Micromechanical mechanism on deterioration of tensile strain capacity of SHCC at negative temperature. Reliability prediction of the tensile strain capacity of SHCC at negative temperatures.